Musculoskeletal Considerations in Female Patients with Chronic Pelvic Pain - Lamvu, Georgine; Carrillo, Jorge; Witzeman, Kathryn; Alappattu, Meryl (Seminars in Reproductive Medicine, 2018)
Persistent pelvic pain conditions are common and affect nearly 25% of the female U.S. population. In a sizable proportion of pelvic pain patients, the pain is caused by musculoskeletal dysfunction; yet, healthcare providers do not routinely evaluate patients for musculoskeletal etiologies. This article provides an overview of the pathophysiology of persistent pelvic pain, as it relates to musculoskeletal disorders. The symptomatology, anatomy, evaluation, and treatment of these disorders are summarized specifically for healthcare providers (including gynecologists) who do not have pelvic musculoskeletal expertise.
Keywords: chronic pelvic pain; pelvic pain; musculoskeletal pain; myofascial